ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL HIGHER ORDER THINKING SKILL (HOTS) MATERI BANGUN RUANG SISI DATAR - Yulianti, Fani; Novtiar, Chandra (IKIP Siliwangi, 2021)
The material for the polyhedron is a primary subject for mathematics that students must learn at the semester VIII junior high school level. However, the reality in the field is that studying the material is still considered difficult by students. Many students have some problems in solving the Higher Order Thinking Skill (HOTS) questions of the material. This research was conducted to examine the factors that cause student errors in answering the HOTS questions on the polyhedron. The method used in this research is descriptive qualitative with research subjects is the IX grade students of SMP Negeri 02 Cipongkor, with a sample from IX-F students, 11 boys, and 17 girls. The data analysis technique used in this research is to analyze the factors that cause student errors in solving the test questions of the data sharing materials and then calculate the percentage score for each question and interpretation based on Arikunto understanding criteria. Based on the results of the study, it was found that the factors that caused student errors in solving the problem were: 1) Students had difficulty in solving problems at the re-examination stage because students could not prove the truth of the answers they had obtained; 2) lack of accuracy in interpreting problems and writing formulas; 3) lack of understanding of prerequisite material; 4) difficulty in determining the length of the cube and cuboid edges; 5) difficulty in calculating the volume and surface area of a trapezoidal prism.